Approaches to anticancer therapy based on modulation of DNA methylation - V. P. Maksimova; J. V. Makus; V. G. Popova; O. G. Usalka; G. A. Belitsky; M. G. Yakubovskaya; K. I. Kirsanov (Сибирский онкологический журнал)
Background. DNA methylation is a crucial mechanism of epigenetic regulation of transcription. Disturbances in DNA methylation mechanism are associated with various malignancies such as acute myeloid leukaemia, breast cancer, prostate cancer, etc. Influencing the functional status of DNA methyltransferases (DNMTs) enzymes and TET family proteins (TETs), which regulate DNA methylation and demethylation, is the basis of epigenetic anticancer therapy approach. In this review, we have considered the challenges and prospects of nucleoside and non-nucleoside inhibitors of DNMTs as well as TETs inhibitors. The results of clinical trials on the efficacy of DNMTs inhibitors used individually and as part of combination chemotherapy conducted over the last 15 years are also evaluated. Material and Methods. Sources were searched in PubMed, ScienceDirect, Web of Science, eLibrary, CyberLeninka. More than 700 publications were used in the analysis, but the review included mainly works of the last 10 years. A number of articles published earlier than 2015 were used for historical reference. Results. The review provides information on current advances in the development and study of epigenetically active compounds whose action is aimed at the regulation of DNA methylation. Data on the in vitro and in vivo effects of agents considered for use in the therapy of various malignancies are presented. In addition, the data of clinical trials of the most promising epigenetic modulators are presented.